2022
DOI: 10.1371/journal.pgen.1010430
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide CRISPR screen identifies DPM1 as a modifier of DPAGT1 deficiency and ER stress

Abstract: Partial loss-of-function mutations in glycosylation pathways underlie a set of rare diseases called Congenital Disorders of Glycosylation (CDGs). In particular, DPAGT1-CDG is caused by mutations in the gene encoding the first step in N-glycosylation, DPAGT1, and this disorder currently lacks effective therapies. To identify potential therapeutic targets for DPAGT1-CDG, we performed CRISPR knockout screens in Drosophila cells for genes associated with better survival and glycoprotein levels under DPAGT1 inhibit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…The workflow described here could be useful to biologists seeking to collect consistent morphometric data on shape, size, and color of features as small as 10 µm. For example, studies of pupal size (Sriskanthadevan-Pirahas et al 2022), wing vein patterning (Alba et al 2021), photoreceptor neurodegeneration (Dalton et al 2022), or eye mosaic or clonal analysis (Merkle et al 2023) could be accelerated by the capacity to image and measure hundreds of samples in a single image. Photographic analysis of pigmentation also preserves population variation, allowing for a variety of different quantitative measurement or qualitative scoring systems to be applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workflow described here could be useful to biologists seeking to collect consistent morphometric data on shape, size, and color of features as small as 10 µm. For example, studies of pupal size (Sriskanthadevan-Pirahas et al 2022), wing vein patterning (Alba et al 2021), photoreceptor neurodegeneration (Dalton et al 2022), or eye mosaic or clonal analysis (Merkle et al 2023) could be accelerated by the capacity to image and measure hundreds of samples in a single image. Photographic analysis of pigmentation also preserves population variation, allowing for a variety of different quantitative measurement or qualitative scoring systems to be applied.…”
Section: Resultsmentioning
confidence: 99%
“…Among these is a century of work to understand the formation of heterochromatin and its role in gene regulation (Elgin and Reuter 2013). Fly eye phenotypes are powerful tools for studying neurodegeneration (McGurk, Berson, and Bonini 2015) and for identifying causal mutations in (and possible treatments of) human disease (Dalton et al 2022;Manivannan et al 2022). Spectrophotometric measurement of eye pigment from homogenized flies is quantitative (Huisinga et al 2016) Swenson et al 2016;Iyer et al 2016;Diez-Hermano et al 2020; but has limited throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic screens are proving to be a powerful tool in identifying new modulators of specific processes. Although several genetics screens performed in the past aimed to identify genes involved in different aspects of ER stress and the UPR pathway [30][31][32][33][34] , to our knowledge this is the first screen performed in iPSC-derived neurons aiming to identify knockouts that are neuroprotective against Tun. Due to their non-mitotic nature, the difficulties in delivering large DNA fragments, the increased silencing of Cas9 and their heterogeneity, iPSC-derived neurons are particularly challenging cells for genetic screens.…”
Section: Discussionmentioning
confidence: 99%
“…Standard methods for identifying genetic modifiers typically involve utilizing natural variation in the population or performing large mutagenesis screens (1). Several recent studies reported modifier screens in animal models of specific CDGs (14)(15)(16). However, with over 150 CDGs, performing similar studies for each CDG is impractical.…”
Section: Introductionmentioning
confidence: 99%
“…A modifier screen and ERC analysis of NGLY1, a deglycosylating enzyme associated with a CDG, identified multiple glycosylation genes showing high ERC with NGLY1, implicating them as potential modifiers (15). A CRISPR screen in cells with reduced DPAGT1 function, the first step in N-glycan synthesis, identified multiple glycosylation genes able to rescue glycosylation defects caused by inhibition of DPAGT1 (14). In yet another study, a yeast model of PMM2-CDG was evolved over 1000 generations to identify genetic changes that increased the viability of the PMM2 mutant yeast strains (16).…”
Section: Introductionmentioning
confidence: 99%